Testing and modelling of hot-rolled steel castellated hollow tubular beams. (December 2021) - Anbarasu, M.; Pandey, Anjali Kumari Pravin Kumar; Longshithung Patton, M.; Carvalho, Hermes
Abstract: Researchers and design engineers are increasingly interested in castellated beams because of their ability to provide greater flexural strength with lower dead loads, as well as provide services and cost-effective structures. The influence of castellation on the bending strength and stiffness of the hot-rolled steel Square Tubular Beams (STBs) and Castellated Tubular Beams (CTBs) with simply supported end conditions were investigated in this study. Totally eight bending tests were carried out on hollow tubular beams with and without castellation under three point bending. The STBs with a nominal steel tube thickness of 2.5 mm are castellated in a hexagonal pattern. The ultimate moments, moment versus mid-span deflection response curves, and failure patterns are provided as part of the test results. The bending tests show that the flexural capacities and stiffness of the hollow tubular sections significantly increased due to the castellation process. Finite element (FE) models of STBs and CTBs were established by including the material and geometric nonlinearity as well as the measured geometric imperfections. The FE models established show good agreement with the experimental test in terms of ultimate bending strength, moment vs. mid-span deflection response, and failure modes.